Hubungan Hiperurisemia pada Saat Masuk Rumah Sakit dengan Defisit Neurologis Pada Kejadian Stroke Iskemik - Hidayah, Nurul; , Dr. Iwan Setiawan, Sp.S, M.Kes (2017)
Background: Stroke is the third most populous of the disease after heart disease and cancer as well as disease causes of disability in the world. A stroke is a disease of the brain form impaired nerve function and local or global emergence of sudden, progressive, and quickly, which can cause sudden neurological deficit and is a result of ischemia or brain nerves circulation hemoragi. Neurological deficits cause factors that spur of the moment are high levels of uric acid. Purpose: the purpose of this research is to know the relationship of the hiperurisemia at the time of entering the hospital with neurological deficits on the incidence of ischemic strokes. Methods: Analytic observational study of non cross sectional approach with experiments, taking of samples with a purposive sampling a number of 36 patients of ischemic stroke, ischemic stroke patients 18 uric acid levels high with neurological deficits and ischemic stroke patients 18 levels of uric acid is normal with neurological deficits in Boyolali Aisha PKU and PKU Muhammadiyah Delanggu. Data obtained from the primary data and secondary data by questionnaire. Results: the number of ischemic stroke sufferers who have high uric acid levels by as much as 18 patients (36%) of the reaction flask 50.0 patients, whereas in patients with normal uric acid levels by as much as 18 patients (36%) of the reaction flask 50.0 patients. The results of the analysis of data obtained the value of p = 0239 and CC = 0.316. Conclusion: the conclusion from this study is there is no relationship between high uric acid levels at the time of entering the hospital with neurological deficits on the incidence of ischemic strokes